Environmental Surveillance of Zoonotic Francisella tularensis in the Netherlands - Janse, Ingmar; van der Plaats, Rozemarijn Q. J.; de Roda Husman, Ana Maria; van Passel, Mark W. J. (Frontiers in Cellular and Infection Microbiology, 2018)
Tularemia is an emerging zoonosis caused by the Gram-negative bacterium Francisella tularensis, which is able to infect a range of animal species and humans. Human infections occur through contact with animals, ingestion of food, insect bites or exposure to aerosols or water, and may lead to serious disease. F. tularensis may persist in aquatic reservoirs. In the Netherland, no human tularemia cases were notified for over 60 years until in 2011 an endemic patient was diagnosed, followed by 17 cases in the 6 years since. The re-emergence of tularemia could be caused by changes in reservoirs or transmission routes. We performed environmental surveillance of F. tularensis in surface waters in the Netherlands by using two approaches. Firstly, 339 samples were obtained from routine monitoring -not related to tularemia- at 127 locations that were visited between 1 and 8 times in 2015 and 2016. Secondly, sampling efforts were performed after reported tularemia cases (n=8) among hares or humans in the period 2013-2017. F. tularensis DNA was detected at 17% of randomly selected surface water locations from different parts of the country. At most of these positive locations, DNA was not detected at each time point and levels were very low, but at two locations contamination was clearly higher. From 7 out of the 8 investigated tularemia cases, F. tularensis DNA was detected in at least one surface water sample collected after the case. By using a protocol tailored for amplification of low amounts of environmental DNA, 10 gene targets were sequenced. Presence of F. tularensis subspecies holarctica was confirmed in 4 samples, and in 2 of these, clades B.12 and B.6 were identified. This study shows that for tularemia, information regarding the spatial and temporal distribution of its causative agent could be derived from environmental surveillance of surface waters. Tracking a particular strain in the environment as source of infection is feasible and could be substantiated by genotyping, which was achieved in water samples with only low levels of F. tularemia present. These techniques allow the establishment of a link between tularemia cases and environmental samples without the need for cultivation.